Biological effects of African yam bean lectins on the cowpea coreid bug, Clavigralla tomentosicollis (Stal) - Okeola, O.G.; Machuka, J. (Oxford University Press, 2001)
The biological effects of affinity purified seed lectin from African yam bean, Sphenostylis stenocarpa (Harms), were tested on Clavigralla tomentosicollis (Stål) in an artificial seed system. S. stenocarpa was extracted from two African yam bean accessions: Enugu 95-3 and Enugu 98-2. Lectins from both accessions were highly toxic to the insect at 1.0% dry weight. For nymphs feeding on Enugu 95-3 and Enugu 98-2, survival ranged from 16.0 to 24.0% and 4.0 to 16.0% at 1.0 and 2.0% dry weight dietary lectin levels, respectively. From 4.0 to 8.0% dry weight of both lectins, no nymph survived up to 6 d after infestation. At 1.0% dry weights of Enugu 95-3 and Enugu 98-2 lectins, there was a significant delay in total developmental time (5.35 and 5.18 d), reduced survival (24.0% and 16.0%), and reduced growth (0.15 ± 0.02 and 0.14 ± 0.01) and resistance (61.85 ± 9.78 and 57.79 ± 3.80) indices, respectively. S. stenocarpa from Enugu 98-2 was the most toxic, with an LD50 of 0.43%, compared with an LD50 of 0.65% for S. stenocarpa from Enugu 95-3. The results of this investigation indicate that there exists in C. tomentosicollis physiological systems vulnerable to African yam bean lectins.